Development of artificial porous media - Yunan, Mat Hussin; Derahman, Mohd. Nawi; Idris, Ahmad Kamal (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1992)
This paper describes the various methods of developing artificial porous media and also presents some results from the preliminary tests already conducted. Firstly, a brief review of the techniques that have been tried before is given. Many types of materials and construction techniques have been tried but the products mostly had weaknesses. Thus the products were only useful for limited application. The objective of this research is to develop a method which can be produced artificial cores with tailor-made characteristics like porosity, permeability and wettability. By producing this artificial porous media we can solve the problem of not having a field core or having to import berea cores.